Coating composition and application thereof

By using a coating composition containing resin units and inorganic particles, the problem of poor bonding of the surface coating of the heat exchange equipment is solved, and good adhesion and heat resistance of the coating are achieved.

CN119432206APending Publication Date: 2025-02-14JIANGXI JUXIAN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411563326.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when coating is provided on the surface of a heat exchange device, the combination of the coating and the surface of the equipment is poor, resulting in the coating being difficult to apply, not coated well or fall off easily.

Method used

A coating composition is used, including a first slurry and a second slurry. The first slurry consists of resin units, which are polymers of polyamines, isocyanates and polyanhydrides. The second slurry contains inorganic particles. Through a specific molar ratio and solid content ratio, the low viscosity and good adhesion of the coating are ensured. sex.

Benefits of technology

Good distribution and adhesion of the coating on the surface of the heat exchange device is achieved, preventing the coating from clogging micropores, and improving the thermal tolerance and longevity of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432206A_ABST
    Figure CN119432206A_ABST
Patent Text Reader

Abstract

The invention provides a coating composition which comprises a first slurry and a second slurry, the first slurry comprises a resin unit with a certain solid content, and the second slurry comprises inorganic particles with a certain solid content; during application, the resin coating liquid generated by mixing the first slurry and the second slurry has the characteristic of low viscosity, and when the resin coating liquid is used for coating the surface of a base body, the resin coating liquid can be better distributed on the surface of the base body to form a protective layer with high adhesive force, so that the protective effect on the base body can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to the field of polymers, and in particular to a coating for surface coating. Background Art

[0002] For example, shell and tube radiators, plate radiators, or spiral radiators are quite common. In the fields of energy, petroleum, chemical industry, food processing, etc., it is understandable that radiators, or heat exchange equipment, are important equipment for transferring heat.

[0003] Typically, the heat exchange equipment described above needs to operate in a harsh working environment, that is, in a high temperature, high pressure, and high corrosion environment; the heat exchange equipment is therefore susceptible to oxidation, corrosion, or wear, resulting in reduced durability, increased maintenance costs, or obstruction of production operations.

[0004] In order to make the heat exchange equipment resist high temperature, high pressure and high corrosion environment, some coatings can be set on the surface of the heat exchange equipment to protect it; after the coating is set, scaling and corrosion can usually be reduced, durability can be improved and even heat transfer efficiency can be improved.

[0005] However, in the prior art, when coating is provided on the surface of the above-mentioned heat exchange equipment, Because the coating liquid has insufficient performance or the coating steps are inappropriate, the coating cannot be well bonded to the surface of the heat exchange equipment, making it difficult to coat the equipment, poorly coated, or easily fall off the equipment after coating. Summary of the invention

[0006] In order to solve the above-mentioned problems, the present invention provides a coating composition, which includes: a first slurry, which has a resin unit, and the resin unit is a polymer of the following resin components, including: Polyamine, isocyanate, and polyanhydride; and a second slurry having inorganic particles; wherein, The molar ratio of the polyamine, the isocyanate, and the polyanhydride is 1:(0.05-0.4): (0.8-1.6).

[0007] In some embodiments, the solid content of the resin unit in the first slurry is 10-20 wt %.

[0008] In some embodiments, the solid content of the inorganic particles in the second slurry is 2-20 wt %.

[0009] In some embodiments, the mass ratio of the first slurry to the second slurry is 1:(0.2-3).

[0010] In some embodiments, the polyamine includes p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(4-aminophenoxy)benzene (TPER), 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (M-TB), 4,4'-diaminobenzanilide (DABA), 9,9-bis(4-aminophenyl)fluorene (BAFL), or any combination thereof.

[0011] In some embodiments, the isocyanate comprises: diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or any combination thereof.

[0012] In some embodiments, the polyanhydride comprises: pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), bisphenol A diether dianhydride (BPADA), 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BTDA), p-phenylene-trimethylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (HPMDA), bicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride (HBPDA), or any combination thereof.

[0013] In some embodiments, the polyanhydride includes a first polyanhydride and a second polyanhydride, wherein the first polyanhydride is 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), and the second polyanhydride is bisphenol A diether dianhydride (BPADA), 3,3'4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), p-phenylene-triphenylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride (HPMDA), dicyclohexyl-3,4,3',4'-tetracarboxylic acid dianhydride (HBPDA), or any combination thereof.

[0014] In some embodiments, the molar ratio of the first polyanhydride to the second polyanhydride is 1:(0.9-1.5).

[0015] In some embodiments, the first slurry further includes a first solvent, wherein the resin unit is dispersed in the first solvent, and the first solvent includes: dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

[0016] In some embodiments, the inorganic particles include silicon nitride, boron nitride, silicon carbide, aluminum oxide, zinc oxide, titanium oxide, magnesium oxide, zirconium oxide, silicon dioxide, or any combination thereof.

[0017] In some embodiments, the second slurry further includes a second solvent, wherein the inorganic particles are dispersed in the second solvent, and the second solvent includes dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

[0018] In some embodiments, the second slurry further includes a silane coupling agent and a curing agent, wherein the silane coupling agent includes: γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, β- (3,4-Epoxycyclohexyl)ethyltrimethoxysilane, or any combination thereof.

[0019] The present invention provides a method for preparing a resin composite, which comprises: S1, obtaining step: Obtain a substrate and a coating composition as described above, which includes the first slurry and the second slurry; S2, a mixing step: mixing the first slurry and the second slurry to obtain a resin coating; and S3, a compounding step: applying the resin coating to the surface of the substrate to obtain a resin composite.

[0020] In some embodiments, the S3, compounding step further includes S31, a heating step: heating the resin coating applied on the surface of the substrate to obtain the resin composite.

[0021] In some embodiments, the S3, compounding step is performed multiple times.

[0022] The present invention provides a resin coating, which is prepared from the coating composition as mentioned above.

[0023] The present invention provides a resin composite, which comprises: a substrate; and a protective layer formed on the surface of the substrate; wherein the protective layer comprises a resin layer, and the resin layer is formed by the resin coating as described above.

[0024] The effects brought by the present invention include but are not limited to: (1) the coating composition has the characteristic of low viscosity. When the coating composition is used in combination to coat the surface of a substrate, the coating composition can be better distributed on the surface of the substrate and is not easy to block the micropores on the surface of the substrate; and (2) regarding the resin composite, wherein the protective layer has good adhesion to the surface of the substrate and good heat tolerance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a flow chart of a first preparation method of a first slurry.

[0026] Figure 2 The present invention is a flow chart of the second preparation method of the first slurry.

[0027] Figure 3 This is a flow chart of the first preparation method of the second slurry.

[0028] Figure 4 The first process flow chart of the resin composite is shown in FIG.

[0029] Figure 5 The second process flow chart of the resin composite is shown in FIG.

[0030] Figure 6 Schematic diagram of the first preparation of the resin composite.

[0031] Figure 7 This is a second schematic diagram of the preparation of the resin composite. DETAILED DESCRIPTION

[0032] The essential features of the present invention are further explained below by combining the accompanying drawings and some embodiments.

[0033] Regarding the relationship between solute and solution or for describing the result of a mixing action, the action term "dispersion" of the present invention means that the result of the action will tend to cause the solute to exist in the solution in a colloidal form; the action term "dissolution" means that the result of the action tends to cause the solute to exist in the solution in a molecular or ionic form.

[0034] In some embodiments, the present invention provides a coating composition comprising: a first slurry, It has a resin unit, which is a polymer of the following resin components, including: polyamine, isocyanate, and polyanhydride; and a second slurry, which has inorganic particles; wherein the molar ratio of the polyamine, the isocyanate, and the polyanhydride is 1: (0.05-0.4): (0.8-1.6).

[0035] In some embodiments, preferably, the molar ratio of the polyamine, the isocyanate, and the polyanhydride is 1:(0.1-0.2):(1.1-1.2).

[0036] In some embodiments, the mass ratio of the polyamine, the isocyanate, and the polyanhydride is 1:(0.5-2.5):(1.0-2.0), preferably 1:(1.0-2.0):(1.0-1.2).

[0037] In some embodiments, the solid content of the resin unit in the first slurry is 10-20wt%, preferably 12-19wt%, and more preferably 14.95-17.58wt%.

[0038] In some embodiments, the solid content of the inorganic particles in the second slurry is 2-20 wt %, preferably 5-15 wt %.

[0039] In some embodiments, the mass ratio of the first slurry to the second slurry is 1: (0.2-3), preferably 1:(0.25-2.5).

[0040] In some embodiments, the resin unit includes: a polyester unit, a polyurethane unit, or a polyimide unit.

[0041] In some embodiments, the resin unit is a polymer of the following resin components, including: Isocyanate, polyol, polyamine, polyanhydride, polyacid, or any combination thereof.

[0042] In some embodiments, the polyamine includes p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(4-aminophenoxy)benzene (TPER), 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (M-TB), 4,4'-diaminobenzanilide (DABA), 9,9-bis(4-aminophenyl)fluorene (BAFL), or any combination thereof.

[0043] In some embodiments, the polyanhydride comprises: pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), bisphenol A diether dianhydride (BPADA), 3,3'4,4'-benzophenone tetracarboxylic dianhydride (BTDA), p-phenylene-triphenylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (HPMDA), dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride (HBPDA), or any combination thereof.

[0044] In some embodiments, the isocyanate includes diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or any combination thereof.

[0045] In some embodiments, the polyanhydride includes a first polyanhydride and a second polyanhydride, wherein the first polyanhydride is 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), and the second polyanhydride is bisphenol A diether dianhydride (BPADA), 3,3'4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), p-phenylene-triphenylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride (HPMDA), dicyclohexyl-3,4,3',4'-tetracarboxylic acid dianhydride (HBPDA), or any combination thereof.

[0046] In some embodiments, the molar ratio of the first polyanhydride to the second polyanhydride is 1:(0.9-1.5), preferably 1:(1.2-1.3).

[0047] In some embodiments, the mass ratio of the first polyanhydride to the second polyanhydride is 1:(8-20), preferably 1:(12-14).

[0048] In some embodiments, the first slurry further includes a first solvent, wherein the resin unit is dispersed in the first solvent, and the first solvent includes: dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

[0049] In some embodiments, for example, in the environment of the first solvent, the dianhydride and the diamine can be polymerized with each other, that is, polyamic acid will be produced after the polymerization reaction; then, the polyamic acid can be dehydrated or the first solvent can be removed to form a solid polyimide, that is, a resin.

[0050] Therefore, it can be understood that the polyimide unit is polyamic acid, which can be dispersed in the first solvent.

[0051] Please refer to Figure 1 In some embodiments, a method for preparing a first slurry is provided. It includes: P1, a dissolving step: dissolving the resin component in the first solvent; and P2, a polymerization step: polymerizing the resin component to form the resin unit; wherein the resin unit is dispersed in the first solvent to form the first slurry together.

[0052] In some embodiments, the P1 dissolution step and the P2 polymerization step are respectively performed in a gas atmosphere, wherein the gas is nitrogen, argon or helium, preferably nitrogen.

[0053] Please refer to Figure 2In some embodiments, the P1, dissolution step further includes: P11, a first dissolution step and P12, a second dissolution step, wherein the P11, the first dissolution step is performed before the P12, the second dissolution step.

[0054] In some embodiments, the resin component further includes: a first resin component, a second resin component, and a third resin component; in some embodiments, the first resin component is a polyamine, the second resin component is a polyanhydride, and the third resin component is an isocyanate.

[0055] In some embodiments, there is more than one first resin component and more than one second resin component.

[0056] In some embodiments, the P11, first dissolution step is: dissolving the first resin component in the first solvent for a first dissolution time, wherein the first dissolution time is at least 30 minutes, preferably 30 to 60 minutes.

[0057] In some embodiments, the P12, second dissolution step is: dissolving the second resin component in the first solvent for a second dissolution time, wherein the second dissolution time is at least 0 minutes but not 0 minutes, and is preferably less than the first dissolution time.

[0058] In some embodiments, in the P2, polymerization step: the resin component is polymerized into the resin unit at a polymerization temperature, wherein the polymerization temperature is 0-50°C, preferably 0-25°C, and more preferably 0-10°C.

[0059] In some embodiments, in the P2 polymerization step: the resin component is polymerized into the resin unit during the polymerization time, wherein the polymerization time is 1-20 hours, preferably 5-15 hours, and more preferably 10 hours.

[0060] In some embodiments, the inorganic particles include silicon nitride, boron nitride, silicon carbide, aluminum oxide, zinc oxide, titanium oxide, magnesium oxide, zirconium oxide, silicon dioxide, or any combination thereof.

[0061] In some embodiments, the second slurry further includes a second solvent, wherein the inorganic particles are dispersed in the second solvent, and the second solvent includes dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

[0062] In some embodiments, the first solvent is the same as or different from the second solvent.

[0063] In some embodiments, the second slurry further includes a silane coupling agent, which includes: an amino silane coupling agent, an epoxy silane coupling agent, a vinyl silane coupling agent, a thiol silane coupling agent, a methacryloxy silane coupling agent, a chloropropyl silane coupling agent, an isocyanate silane coupling agent, an ester silane coupling agent, or any combination thereof.

[0064] In some embodiments, the silane coupling agent includes: γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, or any combination thereof.

[0065] In some embodiments, the commercially available types of silane coupling agents include KH-550, KH791, WD-42, KH-570, A-186, or WD-71.

[0066] In some embodiments, the commercially available model of γ-aminopropyltriethoxysilane is KH-550.

[0067] In some embodiments, the mass of the silane coupling agent accounts for 1 wt % to 7 wt % of the solid content of the second slurry.

[0068] In some embodiments, the second slurry further includes a curing agent, which is hydrophobic or hydrophilic.

[0069] In some embodiments, the curing agent includes: toluene diisocyanate (TD I) curing agent, diphenylmethane diisocyanate (MD I) curing agent, hexamethylene diisocyanate (HD I) curing agent curing agent, isophorone diisocyanate-based (IPDI) curing agent, wood diisocyanate-based (XDI) curing agent, cyclohexane dimethyl diisocyanate-based (H12MDI) curing agent, blocked isocyanate curing agent, or any combination thereof.

[0070] In some embodiments, the curing agent is a blocked isocyanate curing agent, and its commercial model is MF-K60X.

[0071] In some embodiments, the curing agent is (Covestro) products, including models: N100HD I, N3300 HD I, N75 MPA / X HD I, or L75 A / C TD I.

[0072] In some embodiments, the blocked isocyanate curing agent is a composition of compounds having -NCO groups; the blocked isocyanate curing agent accounts for 0.5-5% by weight of the second slurry, preferably 0.8-1.2% by weight.

[0073] In some embodiments, the commercially available model of the blocked isocyanate curing agent is MF-K60X.

[0074] Please refer to Figure 3 In some embodiments of the present invention, a method R for preparing a second slurry is provided, which comprises: R1, a dissolution and dispersion step: dissolving the inorganic particles, the silane coupling agent, and the curing agent in the second solvent, and performing a first dispersion treatment to form the second slurry together.

[0075] In some embodiments, the first dispersing process includes: a first stirring process and / or a first oscillating process.

[0076] In some embodiments, the first dispersion process is a first stirring process and a first oscillation process. Treatment, the first stirring treatment precedes the first oscillation treatment; wherein the time of the first stirring treatment is 0.5 to 3 hours, preferably 1 hour; the time of the first oscillation treatment is 0.5 to 3 hours, preferably 1 hour.

[0077] In some embodiments, the duration of the dispersion process is the same as the duration of the oscillation process.

[0078] It can be understood that the rotation speed of the first stirring process is not limited, and the oscillation frequency of the first oscillation process is not limited.

[0079] Please refer to Figure 4 In some embodiments of the present invention, a method S for preparing a resin composite is provided, which comprises: S1, an obtaining step: obtaining a substrate 10, and obtaining the coating composition as described above, which comprises the first slurry and the second slurry; S2, a mixing step: mixing the first slurry and the second slurry to obtain a resin coating; and S3, a compounding step: The resin coating is applied to the surface of the substrate 10 to obtain a resin composite 1 .

[0080] In some embodiments, the step S2, mixing, further includes: mixing the first slurry and the second slurry, and performing a second dispersion treatment to obtain the resin coating.

[0081] In some embodiments, the second dispersing process includes: a second stirring process and / or a second oscillating process.

[0082] In some embodiments, the second dispersing treatment is a second stirring treatment and a second oscillating treatment, and the second stirring treatment precedes the second oscillating treatment; wherein the time of the second stirring treatment is 0.5 to 3 hours; the time of the second oscillating treatment is 0.5 to 3 hours, preferably 2 hours.

[0083] It can be understood that the rotation speed of the second stirring process is not limited, and the oscillation frequency of the second oscillation process is not limited.

[0084] In some embodiments, the S3, compounding step further includes: applying the resin coating to the surface of the substrate 10 by dipping and / or spraying to obtain the resin composite 1.

[0085] It can be understood that the above-mentioned "coating" of the coating on the surface of the substrate 10 is It can be a combination of dipping and spraying, or only dipping or only spraying. There is no restriction on the coating method.

[0086] In some embodiments, after the resin coating is applied to the surface of the substrate 10 by dipping and / or spraying, there may be a drying or air-drying step.

[0087] Please refer to Figure 5 In some embodiments, the S3, compounding step further includes S31, a heating step: applying the resin coating to the surface of the substrate 10, and heating the resin coating applied to the surface of the substrate 10 to obtain the resin composite 1.

[0088] It can be understood that the heating treatment is to dehydrate or harden the resin coating so that the resin units therein further become resin.

[0089] In some embodiments, the heating treatment in the heating step S31 includes: a first heating treatment and a second heating treatment; in some embodiments, the first heating treatment is performed first, and then the second heating treatment is performed.

[0090] In some embodiments, the heating temperature of the first heating treatment is 120° C. to 150° C. The holding time is 5-20 minutes, preferably 10 minutes; the heating temperature of the second heat treatment is 250°C to 300°C, and the holding time is 5-20 minutes, preferably 10 minutes.

[0091] In some embodiments, between the first heating treatment and the second heating treatment, There is also a first temperature increase treatment, which adopts a step-by-step temperature increase method with a temperature increase rate of 0.5°C to 10°C / minute, preferably 1°C / minute.

[0092] In some embodiments, the S3, compounding step is performed multiple times, which can be 2 times, 3 times, 4 times, or 5 times, or there is no need for limitation.

[0093] In some embodiments of the present invention, a resin coating is provided, which is prepared from the coating composition as described above; specifically, the resin coating is prepared by mixing the first slurry and the second slurry.

[0094] In some embodiments, the resin coating is in a liquid state and may slowly transform into a solid state starting from a point in time; such a transformation includes occurring when the resin coating absorbs a certain degree of heat or reaches a certain degree of temperature; thus, the resin coating can form a resin layer.

[0095] Please refer to Figure 6 In some embodiments, the present invention provides a resin composite 1, The first slurry is prepared by the preparation method S of the resin composite, wherein the first slurry is prepared by the preparation method P of the first slurry, and the second slurry is prepared by the preparation method R of the second slurry.

[0096] In some embodiments of the present invention, a resin composite 1 is provided, which includes: a substrate 10; and a protective layer 11 formed on the surface of the substrate 10; wherein the protective layer 11 includes a resin layer, and the resin layer is formed by the resin coating as described above.

[0097] In some embodiments, the substrate surface has holes or micropores, and the pore size is between about 0.05 mm (millimeter) and 1.5 mm. In some preferred embodiments, the resin coating will not block the holes or micropores when forming the resin layer.

[0098] Please refer to Figure 7 In some embodiments, in the resin composite 1, the substrate 10 is a heat sink, and the protective layer 11 (represented by a dark background) is formed on its surface; it can also be known that the resin composite 1 is prepared by the substrate 10 through the resin composite preparation method S.

[0099] In some embodiments, the radiator includes: a shell and tube radiator, a plate radiator, or a spiral radiator, which is not actually limited.

[0100] The present invention is further explained below by disclosing some specific embodiments.

[0101] The first aspect: the synthesis of the first slurry, including Synthesis Example 1, Synthesis Example 2, Synthesis Example 3, Synthesis Example 4 and Synthesis Example 5.

[0102] Synthesis Example 1: Below 10°C and in a nitrogen atmosphere, take 232.13 g of NMP into a four-necked reaction flask, then take 4.33 g of PDA and 8.01 g of ODA and add them thereto, dissolve them in each other for 0.5-1 hour, then add 1.39 g of TDI, 11.77 g of BPDA, and 15.47 g of BTDA to carry out a polymerization reaction, and the polymerization reaction time is 10 hours.

[0103] Synthesis Example 2: Below 10°C and in a nitrogen atmosphere, 285.81 g of NMP was added to a four-necked reaction flask, and 4.33 g of PDA and 8.49 g of M-TB were added thereto and dissolved in each other for 0.5-1 hour, and then 2.02 g of HDI, 11.77 g of BPDA, and 23.83 g of TAHQ were added to carry out a polymerization reaction, and the polymerization reaction time was 10 hours.

[0104] Synthesis Example 3: At 10°C or below and in a nitrogen atmosphere, take 299.05 g of NMP In a four-necked reaction flask, 11.69 g of TPER and 8.49 g of M-TB were added thereto and dissolved in each other for 0.5-1 hour. Then, 2.69 g of HDI, 11.77 g of BPDA, and 29.15 g of BPADA were added to carry out polymerization reaction. The polymerization reaction time was 10 hours.

[0105] Synthesis Example 4: At a temperature below 10° C. and in a nitrogen atmosphere, 289.69 g of NMP was placed in a four-necked reaction flask, and 11.69 g of TPER and 8.49 g of M-TB were added thereto and dissolved in each other for 0.5-1 hour. Then, 2.69 g of HDI and 28.25 g of BPDA were added to carry out a polymerization reaction. The polymerization reaction time was 10 hours.

[0106] Synthesis Example 5: At a temperature below 10° C. and in a nitrogen atmosphere, 412.78 g of NMP was placed in a four-necked reaction flask, and 11.69 g of TPER and 8.49 g of M-TB were added thereto and dissolved in each other for 0.5-1 hour. Then, 2.69 g of HDI and 49.97 g of BPADA were added to carry out a polymerization reaction. The polymerization reaction time was 10 hours.

[0107] The comparison of the component types and their respective first solid contents of Synthesis Examples 1-5 is shown in Table 1. As shown. Wherein, assuming that the mass of the first solvent is M1, the mass of the first polyamine is N1, the mass of the second polyamine is N2, the mass of the isocyanate is N3, the mass of the first polyanhydride is N4, and the mass of the second polyanhydride is N5, the first solid content (%) is calculated as follows:

[0108] First solid content (%) = ((N1+N2+N3+N4+N5) / (M1+N1+N2+N3+N4+N5))×100%.

[0109] Table 1

[0110] The second aspect: the formation of the second slurry, including Synthesis Example 6, Synthesis Example 7 and Synthesis Example 8.

[0111] Synthesis Example 6: Add 5 g of BN (boron nitride) to 95 g of NMP, add 0.5 g of silane coupling agent (KH-550), and add 1 g of curing agent (MF-K60X), stir for 1 hour using a high-speed disperser, and then oscillate for 1 hour using an ultrasonic oscillator.

[0112] Synthesis Example 7: Add 24 g of BN (boron nitride) to 276 g of NMP, then add 1 g of silane coupling agent (KH-550), and add 3 g of curing agent (MF-K60X), stir for 1 hour using a high-speed disperser, and then oscillate for 1 hour using an ultrasonic oscillator.

[0113] Synthesis Example 8: Add 150 g of BN (boron nitride) to 850 g of NMP, then add 3 g of silane coupling agent (KH-550), and add 10 g of curing agent (MF-K60X), stir for 1 hour using a high-speed disperser, and then oscillate for 1 hour using an ultrasonic oscillator.

[0114] The comparison of the component types and masses of Synthesis Examples 6 to 8 and the solid content of the inorganic particles is shown in Table 2. The mass is L1, and the calculation method of the inorganic particle solid content (%) is:

[0115] Inorganic particle solid content (%) = ((L1) / (K1+L1))×100%.

[0116] Table 2

[0117] The third aspect: the synthesis of the resin composite 1, including Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.

[0118] Example 1: Take 200 g (grams) of Synthesis Example 1 and 50 g (grams) of Synthesis Example 6, The mixture was stirred and mixed, and then ultrasonically vibrated for 2 hours to obtain a first resin coating; wherein, The viscosity of the first resin coating was measured to be 343 cP (centipoise), and the total solid content was 13%. Next, the radiator sample was immersed in the first resin coating using a dip coating method, and was taken out after immersion for 5 minutes, and was hung to dry until no droplets fell, and was placed in a 140°C oven for pre-baking for 10 minutes before being taken out, and the immersion, drying, and pre-baking operations were repeated again until completed 3 times, and then the temperature was increased by 1°C / min in a stepwise manner, and the temperature was increased to a maximum of 300°C, and the first radiator was taken out to obtain; at this point, the first resin layer was formed on the surface of the first radiator.

[0119] Example 2: Take 200 g (grams) of Synthesis Example 2 and 150 g (grams) of Synthesis Example 7, The mixture was stirred and mixed, and then ultrasonically vibrated for 2 hours to obtain a second resin coating; wherein, The viscosity of the second resin coating was measured to be 258 cP (centipoise) and the total solid content was 12%. Next, the radiator sample was immersed in the second resin coating using a dip coating method, and was taken out after immersion for 5 minutes, and was hung to dry until no droplets fell, and was placed in a 140°C oven for pre-baking for 10 minutes before being taken out, and the immersion, drying, and pre-baking operations were repeated again until completed 3 times, and then the temperature was increased by 1°C / min in a stepwise manner, and the temperature was increased to a maximum of 300°C, and the second radiator was taken out to obtain; at this point, a second resin layer was formed on the surface of the second radiator.

[0120] Example 3: Take 200 g (grams) of Synthesis Example 3 and 500 g (grams) of Synthesis Example 7 The mixture was stirred and mixed, and then ultrasonically vibrated for 2 hours to obtain a third resin coating; wherein, The viscosity of the third resin coating was measured to be 97 cP (centipoise) and the total solid content was 10%. Next, the radiator sample was immersed in the third resin coating using a dipping method, and was taken out after immersion for 5 minutes, and was hung to dry until no droplets fell, and was placed in a 140°C oven for pre-baking for 10 minutes before being taken out, and the immersion, drying, and pre-baking operations were repeated again until the completion of 3 times, and then the temperature was increased by 1°C / min in a stepwise manner, and the temperature was increased to a maximum of 300°C, and the third radiator was taken out; at this point, a third resin layer was formed on the surface of the third radiator.

[0121] Comparative Example 1: Only 200g (grams) of Synthesis Example 1 was taken, and the viscosity was measured to be 1325cP (centipoise), the total solid content was 15%, and ultrasonic oscillation was used for 2 hours to obtain the first comparative resin coating. Then, the radiator sample was immersed in the first comparative resin coating by the dip coating method, and was taken out after immersion for 5 minutes, and was hung to dry until no droplets fell, and was placed in a 140°C oven for pre-baking for 10 minutes and then taken out, and the immersion, drying, and pre-baking operations were repeated again until they were completed 3 times, and then the temperature was increased by 1°C / min in a stepwise manner, and the temperature was increased to 300°C at the highest, and the first comparative radiator was taken out; at this point, the surface of the first comparative radiator formed a first comparative resin layer.

[0122] Comparative Example 2: 200 g (grams) of Synthesis Example 4 was taken and the viscosity was measured to be 3450 cP (centipoise). The total solid content was 18%, and ultrasonic oscillation was used for 2 hours to obtain a second comparative resin coating. Then, the radiator sample is immersed in the second comparative resin coating by dipping method, taken out after dipping for 5 minutes, hung in the air to dry until no droplets fall, put into an oven at 140°C for pre-baking for 10 minutes and then taken out, and the dipping, drying and pre-baking operations are repeated again for 3 times, and then the temperature is increased by 1°C / min in steps, and the temperature is increased to 300°C at the highest, and the second comparative radiator is taken out to obtain; at this point, a second comparative resin layer is formed on the surface of the second comparative radiator.

[0123] Comparative Example 3: 200 g (grams) of Synthesis Example 5 was taken and the viscosity was measured to be 3752 cP (centipoise). The total solid content is 18%, and ultrasonic oscillation is used for 2 hours to obtain the third comparative resin coating. Next, the radiator sample is immersed in the third comparative resin coating by the dipping method, and is taken out after immersion for 5 minutes, and is hung in the air to dry until no droplets fall, and is placed in a 140°C oven for pre-baking for 10 minutes and then taken out, and the immersion, drying, and pre-baking operations are repeated again until the completion of 3 times, and then the temperature is increased by 1°C / min in a stepwise manner, and the temperature is increased to 300°C at the highest, and the third comparative radiator is taken out; at this point, the surface of the third comparative radiator is formed with a third comparative resin layer.

[0124] Comparative Example 4: 200 g (grams) of Synthesis Example 1 and 50 g (grams) of Synthesis Example 8 were mixed and stirred, and then ultrasonically vibrated for 2 hours to obtain a fourth comparative resin coating; wherein, The viscosity of the fourth comparative resin coating was measured to be 152 (centipoise) and the total solid content was 18%. Next, the radiator sample was immersed in the fourth comparative resin coating by the dipping method, and was taken out after immersion for 5 minutes, and was hung to dry until no droplets fell, and was placed in a 140°C oven for pre-baking for 10 minutes and then taken out, and the immersion, drying, and pre-baking operations were repeated again until the completion of 3 times, and then the temperature was increased by 1°C / min in a stepwise manner, and the temperature was increased to 300°C at the highest, and the fourth comparative radiator was taken out; at this point, the surface of the fourth comparative radiator was formed with a fourth comparative resin layer.

[0125] Regarding the testing method for solid content, a weighing method is used to analyze the first resin coating, the second resin coating, the third resin coating, the first comparative resin coating, the second comparative resin coating, the third comparative resin coating, and the fourth comparative resin coating described in Examples 1-3 and Comparative Examples 1-4, and the unit of the analysis result is percentage (%).

[0126] Regarding the viscosity testing method, a viscosity analyzer is used to analyze the first resin coating, the second resin coating, the third resin coating, the first comparative resin coating, the second comparative resin coating, the third comparative resin coating, and the fourth comparative resin coating described in Examples 1-3 and Comparative Examples 1-4 using a viscosity testing method generally known to the public, and the unit of the analysis result is centipoise (cP).

[0127] Regarding the testing method of thermal weight loss temperature, a thermogravimetric analyzer is used to analyze the first radiator, the second radiator, the third radiator, the first comparative radiator, the second comparative radiator, the third comparative radiator, and the fourth comparative radiator described in Examples 1-3 and Comparative Examples 1-4 using the thermogravimetric analysis (TGA) method known to the public. The analysis result is the temperature required to achieve a weight loss of 5% under the same heating time, and the unit is degrees Celsius (°C).

[0128] The plugging test refers to the results of whether the corresponding resin layer formed by drying the radiator samples after the radiator samples are coated with resin coating by dip coating in Examples 1-3 and Comparative Examples 1-4 forms plugging holes on the surface of the radiator samples. The size of the holes on the surface of the radiator samples is 1 mm (millimeter).

[0129] Regarding the adhesion test method, it refers to the adhesion analysis of the corresponding resin layers on the surfaces of the first radiator, the second radiator, the third radiator, the first comparative radiator, the second comparative radiator, the third comparative radiator, and the fourth comparative radiator described in Examples 1-3 and Comparative Examples 1-4, which is a hundred-grid test (ASTM D3359), and the analysis results are expressed in levels from 0B (worst adhesion), 1B, 2B, 3B, 4B to 5B (best adhesion).

[0130] The technical features and technical effects of Examples 1-3 and Comparative Examples 1-4 are summarized and presented in Table 3. In which, the mass of the first slurry is set to Q1, the mass of the second slurry is set to Q2, and the slurry mass ratio is (Q1:Q2).

[0131] Table 3

[0132] From Table 1, Table 2, and Table 3, we can understand that:

[0133] First, in terms of the polyanhydride, Synthesis Example 4 and Synthesis Example 5 only contain the first polyanhydride, wherein the first polyanhydride in Synthesis Example 4 is BPDA, and in Synthesis Example 5 is BPADA.

[0134] Further correspondingly, it can be seen that Comparative Example 2 and Comparative Example 3, Comparative Example 2 only uses Synthesis Example 4 as slurry, and Comparative Example 3 only uses Synthesis Example 5 as slurry. Comparative Example 2 and Comparative Example 3 are not ideal in the plugging test and adhesion test, especially the thermal weight loss of Comparative Example 2 is even more unsatisfactory; The results show that among the polyanhydrides, only the first polyanhydride BPDA has the worst effect.

[0135] Comparisons 2 and 3 are further compared with Comparative Example 1. Comparative Example 1 uses Synthesis Example 1 as the first slurry, which improves the adhesion and thermal weight loss results because of the first polyanhydride and the second polyanhydride. It is worth noting that the polyanhydride in Synthesis Example 1 is BPDA and BTDA, which shows that the first polyanhydride BPDA combined with the second polyanhydride can solve the problems of poor adhesion and poor thermal weight loss. However, Comparative Example 1 still has the problem of pore blocking.

[0136] Next, Comparative Example 1 is compared with Examples 1, 2, and 3. The difference between Examples 2 and 3 is that the slurries provided in Examples 1, 2 and 3 further include a second slurry having inorganic particles, so that the resin layer formed in the heat sink solves the pore blocking problem; at this point, looking at Comparative Example 4, it is unable to improve the pore blocking result even with inorganic particles in the absence of a second polyanhydride.

[0137] Therefore, the effects of the present invention include: 1. Improving adhesion by combining the first polyanhydride and the second polyanhydride, wherein the first polyanhydride and the second polyanhydride have specific properties; 2. Further improving the pore blocking problem by inorganic particles based on the co-existence of the first polyanhydride and the second polyanhydride.

[0138] The above are only several preferred embodiments of the present invention, but they cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification should fall within the patent protection scope of the present invention.

Claims

1. A coating composition, characterized in that It includes: A first slurry having a resin unit, wherein the resin unit is a polymer of the following resin components, including: a polyamine, an isocyanate, and a polyanhydride; and The second slurry comprises inorganic particles; wherein: The molar ratio of the polyamine, the isocyanate, and the polyanhydride is 1:(0.05-0.4): (0.8-1.6)。 2. The coating composition according to claim 1, characterized in that The solid content of the resin unit in the first slurry is 10-20 wt %.

3. The coating composition according to claim 1, characterized in that The solid content of the inorganic particles in the second slurry is 2-20 wt %.

4. The coating composition according to claim 1, characterized in that The mass ratio of the first slurry to the second slurry is 1:(0.2-3).

5. The coating composition according to claim 1, characterized in that The polyamine includes: p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(4-aminophenoxy)benzene (TPER), 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (M-TB), 4,4'-diaminobenzanilide (DABA), 9,9-bis(4-aminophenyl)fluorene (BAFL), or any combination thereof.

6. The coating composition according to claim 1, characterized in that The isocyanate includes: diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or any combination thereof.

7. The coating composition according to claim 1, characterized in that The polyanhydride includes: pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), bisphenol A diether anhydride (BPADA), 3,3'4,4'-benzophenonetetracarboxylic anhydride (BTDA), p-phenylene-triphenylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic anhydride (HPMDA), dicyclohexyl-3,4,3',4'-tetracarboxylic anhydride (HBPDA), or any combination thereof.

8. The coating composition according to claim 1, characterized in that The polyanhydride includes a first polyanhydride and a second polyanhydride, wherein the first polyanhydride is 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), and the second polyanhydride is bisphenol A diether dianhydride (BPADA), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (BTDA), p-phenylene-triphenylene dianhydride (TAHQ), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (HPMDA), dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride (HBPDA), or any combination thereof.

9. The coating composition according to claim 8, characterized in that The molar ratio of the first polyanhydride to the second polyanhydride is 1:(0.9-1.5).

10. The coating composition according to claim 1, characterized in that The first slurry further includes a first solvent, wherein the resin unit is dispersed in the first solvent, and the first solvent includes: dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

11. The coating composition according to claim 1, characterized in that The inorganic particles include silicon nitride, boron nitride, silicon carbide, aluminum oxide, zinc oxide, titanium oxide, magnesium oxide, zirconium oxide, silicon dioxide, or any combination thereof.

12. The coating composition according to claim 1, characterized in that The second slurry further includes a second solvent, wherein the inorganic particles are dispersed in the second solvent, and the second solvent includes dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), or any combination thereof.

13. The coating composition according to claim 1, characterized in that The second slurry further includes a silane coupling agent and a curing agent, wherein the silane coupling agent includes: γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, or any combination thereof.

14. A method for preparing a resin composite, comprising: S1. Obtaining step: obtaining a substrate, and obtaining the coating composition according to any one of claims 1 to 13, which comprises the first slurry and the second slurry; S2, mixing step: mixing the first slurry and the second slurry to obtain a resin coating; as well as S3, compounding step: applying the resin coating to the surface of the substrate to obtain a resin composite.

15. The preparation method according to claim 14, wherein: The S3, compounding step further includes S31, a heating step: heating the resin coating applied on the surface of the substrate to obtain the resin composite.

16. The preparation method according to claim 15, wherein: The step S3, compounding, is performed multiple times.

17. A resin coating, which is prepared from the coating composition according to any one of claims 1 to 13.

18. A resin composite comprising: matrix; as well as A protective layer is formed on the surface of the substrate; wherein The protective layer includes a resin layer formed of the resin coating according to claim 17 .

Citation Information

Patent Citations

  • Black polyimide coating and preparation method thereof

    CN116376429A

  • Battery liquid cooling plate coating and preparation method thereof

    CN116875183A

  • Polyimide resin composition and molded body using the same

    JP2017179079A